South African teachers’ attitudes towards working with learners with severe intellectual disabilities in schools for Learners with Special Educational Needs - Johnson, Ensa (University of Pretoria, 2021)
Dissertation (MA (Speech-Language Pathology))--University of Pretoria, 2021.